OXYGEN ISOTOPIC EVOLUTION OF AMOEBOID OLIVINE AGGREGATES IN THE REDUCED CV3 CHONDRITES EFREMOVKA, VIGARANO, AND LEOVILLE - Fagan T.J.; Yurimoto H.; Krot A.N.; Keil K. (My University, 2004)
Amoeboid olivine aggregates (AOAs) from the reduced CV chondrites Efremovka, Vigarano, and Leoville consist of forsteritic olivine, FeNi-metal and a refractory component composed of spinel, Aldiopside, anorthite. Secondary ferrous olivine and alkali-rich minerals (nepheline and sodalite), commonly observed in the oxidized CVs, are rare. Mineralogy and chemical compositions of AOAs are similar to those predicted by equilibrium thermodynamic condensation models, suggesting that AOAs formed primarily by gas-solid condensation over a narrow temperature range, slightly below the temperatures over which most Ca-Al-rich inclusions (CAIs) formed. AOAs in the reduced CVs preserve a 1 -generationO-rich signal ( O 40‰) similar to that observed in many CAIs, suggesting that these refractory objects originated from a common source in the solar nebula. In fact AOAs and many fine-grained CAIs may have formed by the same processes, but at slightly different temperatures, and can be considered a single class of refractory objects. Alteration of the AOAs is manifested by differing extents of O-depletion in original AOA minerals, FeO-enrichment in olivine, and formation of interstitial very fine grained Na-bearing phases. From the six AOAs and one fine-grained, melilite-pyroxene-rich CAI examined in this study, five distinct patterns of alteration were identified. (1) One unaltered AOA from Vigarano is characterized by O-rich forsterite without FeO-rich rims and interstitial Na-bearing phases. (2) Weak alteration in the melilite-pyroxene-rich CAI is characterized by incomplete O-depletion in some melilite and precipitation of Na-bearing phases near the CAI rim. (3) Oxygen isotopic composition and mineralogy are correlated in two AOAs from Leoville with O-rich olivine,O-poor anorthite and a range of intermediate compositions in Al-diopside. This pattern is consistent with model diffusion between original grains and a O-poor reservoir during a relatively short-term ( 60 yr), high-temperature (900–1100°C) event. (4) Original forsterite has been enriched in FeO, but remainedO-rich in one AOA from Vigarano. This result is consistent with the slower rate of diffusion of O than Fe and Mg in olivine. At least some interstitial phases are O-rich, and Na-bearing phases are abundant in this AOA. (5) In contrast, oxygen isotopic composition and Fo-content are correlated in two AOAs from Efremovka. The olivine in these AOAs tends to have forsteritic O-rich cores and FeO-rich O-depleted rims. The general correlation between oxygen isotopic composition and Fo-content is difficult to model by diffusion, and may have formed instead by aqueous dissolution and precipitation along the margins of preexisting olivine grains. Independent evidence for aqueous alteration of the Efremovka AOAs is provided by OH-rich signals detected during ion beam sputtering of some of the O-poor olivine. ElevatedOH-count rates and order of magnitude increases inOH detected during single analyses reflect trapping of an aqueous phase in O-depleted olivine. An elevated OH signal was also detected in one analysis of relatively O-poor melilite in the melilite-pyroxene CAI from Vigarano, suggesting that this object also was altered by aqueous fluid.
Keywords: chondrite